Find the infinite product

Algebra Level 5

Let a 0 = 5 2 a_{0} = \frac{5}{2} and a k = a k 1 2 2 a_{k}= a_{k-1}^2 -2 for k 1 k \ge 1 . Compute:

k = 0 ( 1 1 a k ) \large \prod_{k=0}^\infty \left(1-\dfrac{1}{a_{k}}\right)

If your answer comes in form of x y \dfrac{x}{y} where x x and y y are coprime positive integers, then enter x + y x+y as your answer.


The answer is 10.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Aug 22, 2017

CLAIM 1 a k = 2 2 k + 2 2 k a_k \; = \; 2^{2^k} + 2^{-2^k} for all k 0 k \ge 0

This is proved by induction on k k .

CLAIM 2 k = 0 K a k = 2 3 ( 2 2 K + 1 2 2 K + 1 ) \prod_{k=0}^K a_k \; = \; \tfrac23\big(2^{2^{K+1}} - 2^{-2^{K+1}}\big) for all k 0 k \ge 0 .

This is proved by induction on K K .

CLAIM 3 k = 0 K ( a k 1 ) = 2 7 ( 2 2 K + 1 + 1 + 2 2 K + 1 ) \prod_{k=0}^K (a_k-1) \; = \; \tfrac27\big(2^{2^{K+1}} + 1 +2^{-2^{K+1}}\big) for all k 0 k \ge 0 .

Note that a k + 1 + 1 = a k 2 1 = ( a k 1 ) ( a k + 1 ) a_{k+1}+1 \,=\, a_k^2-1 \,=\, (a_k-1)(a_k+1) , and hence that a k 1 = a k + 1 + 1 a k + 1 a_k - 1 \; = \; \frac{a_{k+1} +1}{a_k + 1} for all k 0 k \ge 0 , so that k = 0 K ( a k 1 ) = a K + 1 + 1 a 0 + 1 = 2 7 ( 2 2 K + 1 + 1 + 2 2 K + 1 ) \prod_{k=0}^K (a_k-1) \; =\; \frac{a_{K+1}+1}{a_0+1} \; = \; \tfrac27\big(2^{2^{K+1}} + 1 + 2^{-2^{K+1}}\big) for all K 0 K \ge 0


Putting this all together, we see that k = 0 K ( 1 1 a k ) = k = 0 K ( a k 1 ) k = 0 K a k = 3 7 × 2 2 K + 1 + 1 + 2 2 K + 1 2 2 K + 1 2 2 K + 1 \prod_{k=0}^K \left(1 - \frac{1}{a_k}\right) \; = \; \frac{\displaystyle \prod_{k=0}^K (a_k-1)}{\displaystyle\prod_{k=0}^K a_k} \; = \; \frac37 \times \frac{2^{2^{K+1}} + 1 + 2^{-2^{K+1}}}{2^{2^{K+1}} - 2^{-2^{K+1}}} and hence, letting K K \to \infty , k = 0 ( 1 1 a k ) = 3 7 \prod_{k=0}^\infty \left(1 - \frac{1}{a_k}\right) \; = \; \frac37 making the answer 3 + 7 = 10 3+7 = \boxed{10} .

@Rahil Sehgal , sorry im writing here, but can u please come on slack

Vilakshan Gupta - 3 years, 9 months ago

@Rahil Sehgal Send the pic on whatsapp

Vilakshan Gupta - 3 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...